Estratégias de comunicação em cenários de plataformização da educação no atual ecossistema midiático - Koltermann, Liana Estela Merladete de Souza Pozeczek (2024)
The present research focuses on communication and education, more specifically in educational technology organizations as emerging organizational contexts, and is delimited in the coevolution of its organizational actors. The central inquiry is framed as follows: "how are communication and education strategically appropriate in organizational contexts platformed with emerging educational technologies?" The rationale for this investigation stems from the proliferation of online course platforms, the establishment and expansion of entities identified as educational technology organizations, and the ensuing coevolution involving key stakeholders, namely educators, students, and platforms. The general objective is to analyze the strategic appropriation of communication and education in emerging and platformed organizational contexts of educational technology.Specific objectives encompass: (I) Assessing the influence of Society 5.0 on communication strategies employed by educational organizations operating within digital platforms; (II) Investigating the process of platformization within educational technology organizations; (III) Characterizing the media landscape in which technological organizations are embedded; and ultimately, (IV) Analyzing the relationships and expectations of organizational actors within platforms as distinct organizational entities. The research employs a Multiple Case Study design, incorporating surveys and observational methods. In a significant convergence of communication, education, and technology, the manifestation of the efficacy of online course platforms unveils authentic instructional ecosystems as novel organizational structures. These structures not only prompt a reconsideration and reconstruction of educational landscapes but also reshape organizational communication itself. The latter undergoes a transformation, functioning in tandem with coevolving media paradigms.